Special Economic Zones and agriculture with increasing returns - Soumyatanu Mukherjee (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2013)
This note shows that in a developing economy, agriculture and Special Economic Zones (SEZ) can grow simultaneously without affecting one another if an appropriate subsidy policy is designed by the government. We consider increasing returns brought about by external economies of scale in the SEZ-led industrial sector with a Dixit-Stiglitz production function where resource used to produce each variety of the SEZ-good is itself produced using constant returns to scale (CRS) technology and CRS is also present in the agricultural sector.
Keywords: C65; F12; F13; F16; J33; J43; Q17; 330; Special Economic Zones; Increasing Returns; External Economies of Scale; Dixit-Stiglitz type Production Function